In Vitro Antioxidant and Anticancer Activity of Flavonoid Fraction from the Aerial Parts of Cissus quadrangularis Linn. against Human Breast Carcinoma Cell Lines. (25th August 2013) - Vijayalakshmi, A.; Kumar, P. R.; Sakthi Priyadarsini, S.; Meenaxshi, C.
Abstract : Aim . The present study aimed to isolate flavonoid fraction from the aerial parts of Cissus quadrangularis and to evaluate its antioxidant and anticancer potential using in vitro assay system. Methods . Total phenolic and flavonoid contents were calculated for the drug. Flavonoid fraction was isolated using column chromatography and analysed using HPLC. In vitro, antioxidant activity of the ethanol extract and isolated flavonoid fraction was investigated by nitric oxide, DPPH and hydroxyl radical scavenging assays. Breast cancer (MCF 7) cell line was used as the in vitro cancer model for MTT assay. Result . The amount of total phenolic content and total flavonoid content in the ethanol extract showed 28.6 mg/g dry weight expressed as gallic acid equivalents, and 15.8 mg/g was expressed as quercetin equivalents, respectively. The tested extract showed good dose-dependent free radical scavenging property in all the models with the IC50 values of 98  μ g/mL, 125  μ g/mL, and 96  μ g/mL for ethanol extract and 10  μ g/mL, 12  μ g/mL, and 10  μ g/mL for flavonoid fraction, respectively. The flavonoid fraction possess potent anticancer property against breast cancer cells (MCF7) with IC50 value of 40  μ g/mL. Conclusions . It can be concluded that the aerial part of Cissus quadrangularis has potential antioxidant and anticancer activities.